O7 The diagnosis and treatment of chlamydia and gonorrhoea in general practice in England: analysis of electronic health records and surveillance data. (23rd May 2012) - Wetten, S; Yung, M; Mercer, C; Cassell, J; Hughes, G
Abstract : Background: Primary care has become increasingly important in STI management in England but data on diagnosis and treatment in this setting are not routinely analysed. Aims: To investigate and assess the diagnosis and treatment of bacterial STIs in general practice (GP). Methods: We calculated age and gender standardised estimates of the incidence of diagnoses of chlamydia and gonorrhoea in GP using data from the GP Research Database and national population statistics for the years 2003–2008. Since diagnoses made and treated elsewhere can be recorded in primary care notes, we estimated cases treated in primary care using an algorithm to identify appropriate prescriptions within defined window periods, accounting for other possible treatment indications. We estimated the proportion of all cases reported in England which were treated in GP, relative to other providers of sexual health services. Results: An estimated 21 423 diagnoses of chlamydia (42.3/100 000 registered population) and 1494 diagnoses of gonorrhoea (2.96/100 000) were made in GP in England/annum between 2003 and 2008. 35% of chlamydia diagnoses were in those over 25 years. 70% of chlamydia and 36% of gonorrhoea diagnoses recorded in GP were treated, comprising respectively 12% and 3% of all cases diagnosed in England. Doxycycline and azithromycin were most commonly prescribed drugs for chlamydia. Despite revision of gonorrhoea treatment guidelines in 2005, quinolones remained most commonly prescribed for gonorrhoea (42% in 2006–2008), although the proportion treated with cephalosporins rose gradually over the study period (29% in 2006–2008). The algorithm identified 12% and 30% more treated cases of chlamydia and gonorrhoea compared with including same-day prescriptions only. Conclusions: General practice makes an important contribution to the diagnosis and treatment of bacterial STIs. Efforts to ensure GPs are aware of and use recommended treatment guidelines are needed.